2010
DOI: 10.1007/s00520-010-0987-6
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of CRP, IL-8, PCT, and sTREM-1 in the detection of bacterial infections in pediatric oncology patients with febrile neutropenia

Abstract: PurposeIn this study, we evaluated C-reactive protein (CRP), interleukin (IL)-8, procalcitonin (PCT), and soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) as predictors for bacterial infection in febrile neutropenia, plus their usefulness in febrile neutropenia during chemotherapy-induced gastrointestinal mucositis.MethodsPlasma was obtained from pediatric oncology patients at presentation with febrile neutropenia (n = 43) and 24–48 h later (n = 17). The patients were classified as having or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 37 publications
4
42
1
2
Order By: Relevance
“…[12,13] Though CRP is widely used as a marker for bacterial infection, it has several disadvantages including delayed increase and low specificity. [14] Akin to our study, Urbonas et al, [15] demonstrated high NPV on day 1 for IL-6 and IL-8 (89% and 82%, respectively) for exclusion of bacteraemia/sepsis in 61 episodes of FN. The authors concluded that IL-6/8 and IL-8 could not reliably predict bacterial infection because of low sensitivity and PPV; however, they could be useful for excluding patients with bacteraemia or clinical sepsis.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…[12,13] Though CRP is widely used as a marker for bacterial infection, it has several disadvantages including delayed increase and low specificity. [14] Akin to our study, Urbonas et al, [15] demonstrated high NPV on day 1 for IL-6 and IL-8 (89% and 82%, respectively) for exclusion of bacteraemia/sepsis in 61 episodes of FN. The authors concluded that IL-6/8 and IL-8 could not reliably predict bacterial infection because of low sensitivity and PPV; however, they could be useful for excluding patients with bacteraemia or clinical sepsis.…”
Section: Discussionsupporting
confidence: 52%
“…Similar to our study, they found high NPV (≥95) but a low PPV (≤38) for IL-6 and IL-8 for predicting serious infection. [16] In a contrasting study, Miedema et al, [14] reported IL-8 to be a sensitive (92%) marker for the early detection of bacterial infection. Oude Nijhuis et al, [17] reported a successful application of IL-8 along with objective clinical parameters in identification of low-risk patients, allowing antibiotics to be withheld.…”
Section: Discussionmentioning
confidence: 98%
“…L'Il-6 n'est toutefois pas accessible à tous les centres prenant en charge les patients en NF [14][15][16][17]. Concernant la PCT, un taux initial (lors de la prise en charge de la NF) supérieur à 0,2 mg/mL est retenu comme limite significative d'un risque avéré de bactériémie [18,19]. Cette stratification des patients selon leur risque infectieux a eu pour effet de voir apparaître des propositions d'adaptation d'antibiothérapie chez les patients à faible risque de complication infectieuse : monothérapie parentérale, traitement parentéral en ambulatoire, traitement par voie orale d'emblée initié en milieu hospitalier avec sortie précoce, traitement par voie orale en relais d'une antibiothérapie parentérale avec sortie pré-coce au domicile.…”
Section: Discussionunclassified
“…A wide spectrum of nonroutine laboratory characteristics has been studied as potential biomarkers for bacteremia and other adverse events in pediatric fever in neutropenia in five recent small to mediumsized prospective single-center studies [32][33][34][35][36]. The interested reader is referred to an up-to-date metaanalysis covering 25 studies on 14 biomarkers in 3585 fever in neutropenia episodes [37 & ].…”
Section: Nonroutine Laboratory Testsmentioning
confidence: 99%